2009
DOI: 10.4049/jimmunol.0900471
|View full text |Cite
|
Sign up to set email alerts
|

An Anti-Inflammatory Role for Plasmacytoid Dendritic Cells in Allergic Airway Inflammation

Abstract: It was previously shown that administration of recombinant human Fms-like tyrosine kinase receptor-3 ligand (Flt3L) before allergen challenge of sensitized mice suppresses the cardinal features of asthma through unclear mechanisms. Here, we show that Flt3L dramatically alters the balance of conventional to plasmacytoid dendritic cells (pDCs) in the lung favoring the accumulation of pDCs. Selective removal of pDCs abolished the antiinflammatory effect of Flt3L, suggesting a regulatory role for these cells in on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
146
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 157 publications
(164 citation statements)
references
References 68 publications
(76 reference statements)
15
146
2
1
Order By: Relevance
“…38,39 As shown in Figure 6I, TLR9 transcript levels in untreated DCs derived from asthmatic mice before and on days 7, 14, and 28 after conidia were unchanged from TLR9 levels in DCs derived from naïve mice. The addition of CpG to cultures of DCs derived on day 7 after conidia challenge increased TLR9 transcript levels approximately 2.5-fold higher than TLR9 levels in naïve DCs.…”
Section: Tlr9 Expression and Cpg Responsiveness Do Not Correlate Durimentioning
confidence: 89%
“…38,39 As shown in Figure 6I, TLR9 transcript levels in untreated DCs derived from asthmatic mice before and on days 7, 14, and 28 after conidia were unchanged from TLR9 levels in DCs derived from naïve mice. The addition of CpG to cultures of DCs derived on day 7 after conidia challenge increased TLR9 transcript levels approximately 2.5-fold higher than TLR9 levels in naïve DCs.…”
Section: Tlr9 Expression and Cpg Responsiveness Do Not Correlate Durimentioning
confidence: 89%
“…Others have addressed this question before by using CpG-matured BM-DCs, which are similar to LPS for the instruction of Th1-cell responses, but without effects on asthma [69]. Lambrecht's group has shown that rather plasmacytoid DCs may be able to control asthma [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…Others have addressed this question before by using CpG-matured BM-DCs, which are similar to LPS for the instruction of Th1-cell responses, but without effects on asthma [69]. Lambrecht's group has shown that rather plasmacytoid DCs may be able to control asthma [70,71].Semi-mature DCs prevented the paralyzing symptoms in the EAE model by immune deviating toward a Th2/Tr1 protective response, whereas LPS-matured DCs were not protective [33,72,73]. However, the application of semi-mature DCs in Th2-cell associated asthma model neither ameliorated nor worsened the disease symptoms, similarly to the previous data obtained for the murine L. major Th2-cell infection model [34].…”
mentioning
confidence: 99%
“…Several investigators have shown that lung DC [9,43,54] or GM-CSF-cultured bonemarrow derived DC injected into the lung [55] are able to induce the typical Th2 response to inhaled allergen. Adoptive transfer studies showed that it is mainly the SIRPa 1 CD11b 1 lung DC that are efficient at Th2 priming, whereas Flt3L-cultured cDC are not [6,8]. The exact role of the CD11b À CD103 1 lung cDC in allergic sensitization or tolerance induction is a subject for further study.…”
Section: The Role Of Lung DC Subsets In Allergy and Asthmamentioning
confidence: 97%
“…Immediately below, the lamina propria contains CD11b hi cDC [3][4][5] that express the SIRPa molecule (a ligand of CD47), and the CX3CR1 fractalkine receptor [6,7]. The conducting airways also contain pDC, best identified by additional staining for Siglec-H, or bone-marrow stromal antigen-2 (BST2) [1,2,8,9].…”
Section: Introducing Lung DC Heterogeneitymentioning
confidence: 99%